2016
DOI: 10.1055/s-0036-1593410
|View full text |Cite
|
Sign up to set email alerts
|

Reference Ranges of Fetal Cerebral Lateral Ventricle Parameters by Ultrasonography

Abstract: Objectives This study was done to evaluate the normal fetal cerebral lateral ventricle dimensions with transabdominal ultrasonography. The atrial width (AW), ventricle-tochoroid measurement (V-C), ventricle-to-hemisphere ratio (VHR), and combined anterior horn measurement (CAHM) were taken. Methods This was a cross-sectional study involving 400 normal singleton pregnant subjects whose gestational ages were between 14 and 40 weeks. Transabdominal sonography was performed to obtain the values of the fetal cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Excluded studies and reasons for exclusion are reported in Table S3 . Finally, 42 studies, reported between January 1970 and 2021, met the inclusion criteria, and these provided data for 45,626 fetuses, included in the final analysis ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The median sample size of participating fetuses was 372.5 (range: 50 to 8313; 25th percentile: 175.8; 75th percentile: 709.3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excluded studies and reasons for exclusion are reported in Table S3 . Finally, 42 studies, reported between January 1970 and 2021, met the inclusion criteria, and these provided data for 45,626 fetuses, included in the final analysis ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The median sample size of participating fetuses was 372.5 (range: 50 to 8313; 25th percentile: 175.8; 75th percentile: 709.3).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported more than one fetal brain structure [ 9 , 10 , 17 , 32 , 34 , 36 , 41 , 42 , 43 ]. In addition, 4 studies reported charts for POF [ 9 , 10 , 17 , 36 ], 6 for SF [ 9 , 10 , 17 , 35 , 36 , 44 ], 3 for AV [ 22 , 36 , 43 ], 14 for PV [ 7 , 8 , 14 , 19 , 23 , 26 , 27 , 30 , 32 , 34 , 36 , 38 , 40 , 43 ], 20 for TCD [ 12 , 15 , 16 , 18 , 20 , 21 , 24 , 25 , 28 , 31 , 32 , 34 , 39 , 41 , 42 , 43 , 45 ,…”
Section: Resultsmentioning
confidence: 99%
“…Gravidity was defined as the sum of all pregnancies (including all live births and pregnancies that terminated at <6 months or did not result in a live birth) (14) . The subdivisions of gravidity were: primigravida (first pregnancy), multigravida (2-5 pregnancies), and grandmultigravida (>5 pregnancies) (15) .…”
Section: Methodsmentioning
confidence: 99%
“…Antenatally, at the age of 18 weeks estimated gestation age, the atrial width for the lateral ventricles was 10 mm and 11 mm on the right and on the left respectively and remained so until the time of delivery. According to reference ranges of fetal ventricle size by ultrasound provided by Ishola et al, our patient's measurements were above the 95 th percentile [7]. Unfortunately images of hydrocephalus were not provided in the records.…”
Section: Clinical Observation and Imaging Findingsmentioning
confidence: 83%
“…None of the patients was reported to have hydrocephalus [6]. In a case study by Fauz et al, 166 cases with CDH were reviewed, 4 of them had hydrocephalus [7]. Nineteen cases reviewed by Baglaj et al showed 2 of the patients who had CDH had associated hydrocephalus and none of the cases with DA had hydrocephalus [1].…”
Section: Discussionmentioning
confidence: 99%